A Randomized Controlled Trial of the Effect of 0.01% Atropine Eye Drops Combined with Auricular Acupoint Stimulation on Myopia Progression. (11th August 2021) - Kong, Xie-He; Zhao, Yue; Chen, Zhi; Zeng, Li; Han, Rong; Dong, Xiao-Qing; Guo, Xiao-Cong; Shi, Zheng; Yang, Guang; Yang, Yan-Ting; Zhang, Dan; Zhou, Xing-Tao; et al.
Abstract : Background . Use of 0.01% atropine eye drops (0.01% A) is one of the most common treatments for myopia control for children in Asia. Auricular acupoint stimulation (AAS) was reported to enhance the effect of higher-concentration atropine (0.25%, 0.125%) on myopia control. This study was designed to compare the effect of 0.01% A combined with AAS and 0.01% A alone on myopia progression and choroidal thickness in children. Methods . A total of 104 children were stratified by age and randomly assigned at 1 : 1 to receive 0.01% A or 0.01% A + AAS treatment for 6 months. Repeated measurements of cycloplegic spherical equivalent (SE) autorefraction, axial length (AL), and choroidal thickness were performed at baseline, 1 month, 3 months, and 6 months. Results . The adjusted mean SE change over the 6 months was −0.38 ± 0.04 D in the 0.01% A group ( n  = 50) and −0.25 ± 0.04 D in the 0.01% A + AAS group ( n  = 50), demonstrating a significant between-group difference (P  = 0.02). There was no statistically significant difference in the change of AL and choroidal thickness between the two groups (both P  > 0.05). Conclusions . Adjunctive AAS compared with 0.01% A monotherapy slowed myopic progression in Chinese children by a statistically small amount, but had no effect on axial elongation and choroidal thickness during this 6-month observation. The trial is registered with ChiCTR1900021316 .